Troubled Worker Militancy: Challenges Confronting Western Industrial Relations - Barkin, Solomon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper presents some thoughts on the development of Western industrial relations Systems since the postwar years and dwells on the questions the unions are now facing.